Cardiac rehabilitation: socially deprived patients are less likely to attend but patients ineligible for thrombolysis are less likely to be invited. Issue 3 (1st September 1999) - Melville, M R; Packham, C; Brown, N; Weston, C; Gray, D
Abstract : OBJECTIVE: To identify factors associated with the uptake of cardiac rehabilitation following acute myocardial infarction. DESIGN: Retrospective analysis using multivariate logistic regression modelling. SETTING: Two large teaching hospitals in Nottingham. PATIENTS: Cohorts of patients admitted with acute myocardial infarction in 1992 and 1996. INTERVENTIONS: None. MAIN OUTCOME MEASURES: Factors in multivariate analysis found to be associated with attendance at cardiac rehabilitation. Use of secondary prevention in those who were and were not invited and those who did and did not attend cardiac rehabilitation. RESULTS: 58% of all patients were offered cardiac rehabilitation. Attendance rates were 60% in 1992 and 74% in 1996. Invitations were more likely to be offered to younger patients, those who had received thrombolysis, and to patients admitted to one of the two Nottingham hospitals. Use of secondary prevention was only 48% in 1992 but this increased to 80% in 1996. Patients not receiving secondary prevention were less likely to be invited to cardiac rehabilitation. Social deprivation was the only factor significantly associated with poor uptake of cardiac rehabilitation in both years. There was no difference in the use of secondary prevention between those who did and did not attend cardiac rehabilitation. CONCLUSION: Those invited to attend a cardiac rehabilitation programme are likely to be in a good prognosis group, comprising those who are young and have received thrombolysis. Those at greatest risk, particularly patients from socially deprived areas, seem to be missing out on the potential benefits of cardiac rehabilitation. High risk patients should be specifically targeted to ensure that they are invited to, and encouraged to, attend a programme of cardiac rehabilitation.